MiR-100 is a predictor of endocrine responsiveness and prognosis in patients with operable luminal breast cancer. Issue 5 (29th October 2020) - Petrelli, Annalisa; Bellomo, Sara Erika; Sarotto, Ivana; Kubatzki, Franziska; Sgandurra, Paola; Maggiorotto, Furio; Di Virgilio, Maria Rosaria; Ponzone, Riccardo; Geuna, Elena; Galizia, Danilo; Nuzzo, Anna Maria; Medico, Enzo; et al.
Abstract : Purpose: Overexpression of miR-100 in stem cells derived from basal-like breast cancers causes loss of stemness, induction of luminal breast cancer markers and response to endocrine therapy. We, therefore, explored miR-100 as a novel biomarker in patients with luminal breast cancer. Methods: miR-100 expression was studied in 90 patients with oestrogen-receptor-positive/human-epidermal growth factor receptor 2-negative breast cancer enrolled in a prospective study of endocrine therapy given either preoperatively, or for the treatment of de novo metastatic disease. Response was defined as a Ki67 ≤2.7% after 21±3 days of treatment. The prognostic role of miR-100 expression was evaluated in the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) and The Cancer Genome Atlas (TCGA) breast cancer datasets. Additionally, we explored the correlation between miR-100 and the expression its targets reported as being associated with endocrine resistance. Finally, we evaluated whether a signature based on miR-100 and its target genes could predict the luminal A molecular subtype. Results: Baseline miR-100 was significantly anticorrelated with baseline and post-treatment Ki67 (p<0.001 and 0.004, respectively), and independently associated with response to treatment (OR 3.329, p=0.047). In the METABRIC dataset, high expression of miR-100 identified women with luminal A tumours treated with adjuvant endocrine therapy with improved overall survival (HR 0.55, p<0.001). miR-100 was negatively correlated with PLK1, FOXA1, mTOR and IGF1R expression, potentially explaining its prognostic effect. Finally, a miR-100-based signature developed in patients enrolled in the prospective study outperformed Ki67 alone in predicting the luminal A phenotype. Conclusions: Our findings suggest that miR-100 should be further explored as a biomarker in patients with luminal breast cancer.